2021
DOI: 10.1109/ojcas.2020.3042463
|View full text |Cite
|
Sign up to set email alerts
|

Toward Intelligent Reconfigurable Wireless Physical Layer (PHY)

Abstract: Next-generation wireless networks are getting significant attention because they promise 10factor enhancement in mobile broadband along with the potential to enable new heterogeneous services. Services include massive machine type communications desired for Industrial 4.0 along with ultra-reliable low latency services for remote healthcare and vehicular communications. In this article, we present the design of intelligent and reconfigurable physical layer (PHY) to bring these services to reality. First, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The drawback of the design is that it uses a lower-end FPGA with a static approach. 93 Dou and Zhang built OFDM on STM32F407, a microcontroller-based ARM Cortex-M4 processor, and reported the 256 FFT and IFFT with a floating-point execution time of 2.88 ms. The design has a lower microcontroller and is slow for computation.…”
Section: Ribeiro Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawback of the design is that it uses a lower-end FPGA with a static approach. 93 Dou and Zhang built OFDM on STM32F407, a microcontroller-based ARM Cortex-M4 processor, and reported the 256 FFT and IFFT with a floating-point execution time of 2.88 ms. The design has a lower microcontroller and is slow for computation.…”
Section: Ribeiro Andmentioning
confidence: 99%
“…Singh et al implemented OFDM with 16 QAM and 64 FFT, explored the reconfigurability, and observed an execution duration of 700 ms. The drawback of the design is that it uses a lower‐end FPGA with a static approach 93 . Dou and Zhang built OFDM on STM32F407, a microcontroller‐based ARM Cortex‐M4 processor, and reported the 256 FFT and IFFT with a floating‐point execution time of 2.88 ms.…”
Section: Comparative Analysis Of Mimo‐ofdm System Architecturementioning
confidence: 99%
“…Various studies and experiments have demonstrated that conventional frameworks such as Shannon theory [30], detection theory [31], and queuing theory [32] based wireless PHY suffer from performance degradation due to randomness and diversity of wireless environments. Instead of exploring approximate frameworks, recent advances in AI-MDL approaches and their ability to address hard-to-model problems offer a good alternative for making the wireless PHY robust [33] [34]. Numerous works have shown that traditional ML techniques have been successful in combating complex wireless environments and hardware non-linearities [21].…”
Section: Literature Review: DL In Wireless Phymentioning
confidence: 99%